Toward High‐Speed Nanoscopic Particle Tracking via Time‐Resolved Detection of Directional Scattering. Issue 9 (5th August 2020) - Beck, Paul; Neugebauer, Martin; Banzer, Peter
Abstract: Owing to their immediate relevance for high precision position sensors, a variety of different sub‐wavelength localization techniques has been developed in the past decades. However, many of these techniques suffer from low temporal resolution or require expensive detectors. Here, a method is presented that is based on the ultrafast detection of directionally scattered light with a quadrant photodetector operating at a large bandwidth, which exceeds the speed of most cameras. The directionality emerges due to the position dependent tailored excitation of a high‐refractive index nanoparticle with a tightly focused vector beam. A spatial resolution of 1.1 nm and a temporal resolution of 8 kHz is reached experimentally, which is not a fundamental but rather a technical limit. The detection scheme enables real‐time particle tracking and sample stabilization in many optical setups sensitive to drifts and vibrations. Abstract : The high‐precision, ultrafast localization of single nanoparticles is of general importance for the whole field of nanometrology. Here, the position of a single dielectric nanoparticle is determined with ultrahigh spatial and temporal resolution. The detection of light scattered from the particle upon excitation with a structured light beam makes it possible to reconstruct its trajectory.